Legal Education in the Technology Revolution: The evolutionary nature of computer-assisted learning - Maree Chetwin; Cally Edgar (Legal Education Review)
In 1998 the Law Society of Western Australia banded together with Women Lawyers of Western Australia to commission a consultant to “better understand the reasons for the apparently high rate of people leaving the legal profession” in Western Australia. A Final Report was published the following year.1 The Report investigates why young lawyers, particularly women lawyers, were exiting legal practice within the 3–7 year post admission stage. The Report’s findings are not altogether surprising. They show that lack of fulfilment, stress, onerous working conditions and general quality of life issues are the key factors behind the migration from legal practice.